Aplicação dos métodos AHP e fuzzy TOPSIS em incubadoras de empresas - Patias, Jovani (2017)
Given the importance of the process of organizational analysis and decision making, as a way to optimize results and to face business competitiveness, business incubators appear as promoters and executors of advisory programs, both in business management and in questions of technical character. Considering the importance of the companies for the development of the nation and the need to reduce mortality rates, the investment in incubators is justified, since, statistics indicate that the mortality rate among companies that go through the incubation process is approximately, 20% in the first year, compared to 70% among those companies born outside the incubator environment. Therefore, this dissertation was structured based on the following study question: What are the criteria that most influence the business competitiveness of business incubators? In order to solve this problem, the general objective was to determine, through AHP and Fuzzy TOPSIS methods, such criteria in three incubators of companies without a northwestern region of Rio Grande do Sul, through the studies of George A. Steiner (1969). The development of this study was divided into three phases: (1) theoretical review (2) data collection (3) analysis and interpretation of data and presentation of diagnosis. As far as methodological procedures are concerned, the research was characterized as exploratory, through the study of multiple cases integrated in three incubators of companies, through the application of structured questionnaires with the managers of the incubators. As a result, the interviewees understanding of the business competitiveness through their prioritization, through the AHP method, as well as the performance of the incubators against the weights of the criteria in studies, analyzed through the fuzzy TOPSIS method, was highlighted. Thus, it was concluded that the applicability of the methods in studies as a qualifier of the decision-making process was salutary, promoting a better understanding of the development of the objects in studies and the region.